Pengaruh Terapi Inhalasi Sederhana Untuk Meningkatkan Bersihan Jalan Napas pada Anak Dengan ISPA di Wilayah Puskesmas Bugangan Kota Semarang - Erni Suprapti; Yuni Astuti; Tuti Anggarawati (Jurnal Ilmu Kesehatan dan Gizi, 2024)
ARI is an acute respiratory disease characterized by signs of cough, runny nose, hoarseness, fever and discharge of mucus or mucus that lasts up to 14 days. The impact of ARI begins with the interaction of the virus with the body, viral irritation that causes damage to the structure of the lining of the respiratory tract which results in increased activity of the mucus glands in the walls of the respiratory tract, resulting in the release of mucosal fluid that exceeds normal and the problem that arises is ineffective airway clearance. The application of simple inhalation using eucalyptus oil can improve airway clearance in ARI patients. The purpose of this study was to analyze the effect of simple inhalation on improving airway clearance in children with ARI. The research method is experimental with a pre-post test design. The study was conducted by assessing airway clearance before and after simple inhalation therapy. The sample size in the study was 30 respondents determined by purposive sampling. The results of the study to be achieved in the form of a textbook integrated with the learning outcomes of the Pediatric Nursing course, HAKI, and national publications. The TKT target of this study is at level 2. The results of this study indicate that there is an effect of simple steam inhalation in improving airway clearance in children with ARI with a p value of 0.000. The conclusion of this study shows that simple steam inhalation can improve airway clearance in children with ARI. The suggestion of this study can be used as a guide for mothers at home who have children who experience ineffective airway clearance due to ARI.